Pengaruh Financial Literacy dan Investment Experience terhadap Risk Tolerance dan Investment Decision - Nur Asfira; Andewi Rokhmawati; Ahmad Fauzan Fathoni (Jurnal Ekonomi, 2019)
Data from the pre-survey results indicated that financial literacy, investment experience was in average good. While in risk-taking, investors tend to take low risks in making investment decisions. This study aims to determine the effects to financial literacy and investment experience on risk tolerance and investment decisions. The sampling technique that has been chosen is an incidental method that is giving an opportunity to the entire population to be sampled but will be re-elected according to the characteristics of 160 respondents. Primary data is collected by questionnaire as an instrument to prove the results of research, to test the hypothesis in the study is to use path analysis with the help of the SPSS program. The results of this study indicate that financial literacy and investment experience has a negative and significant effect on risk tolerance. Financial literacy and investment experience have a positive and significant effect on investment decision. Risk tolerance able to mediate the influence of financial literacy and investment experience on investment decisions. Risk tolerance has a negative and significant effect on investment decision. a good investment decision is influenced by the level of financial knowledge, investment experience, and risk analysis of the investor.